2020
DOI: 10.3390/cancers12020471
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGF-β1 Polymorphisms with Breast Cancer Risk: A Meta-Analysis of Case–Control Studies

Abstract: Reports on the association of TGF-β1 polymorphisms with breast cancer (BC) have been conflicting, inconsistent, inconclusive, and controversial. PubMed, EMBASE, and Google Scholar were used to identify studies on TGF-β1 polymorphisms and BC risk. Data were extracted independently, and of the initial 3043 studies, 39 case-control studies were eligible for inclusion in the meta-analysis. Information from these studies was extracted, and the overall associations of three TGF-β1 polymorphisms (TGF-β1 29>T/C, TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The extra recognition site in the mRNA results in significantly more suppression of the target. In line with TGF-β acting as a tumour suppressor during the early stages of cancer development, a meta-analysis of 39 case–control studies indicated that rs1982073 was significantly associated with breast cancer risk in the Asian population [ 173 ]. In addition to SNPs affecting miRNA:mRNA target recognition, SNPs can also influence the degree of silencing.…”
Section: Mirna Dysregulation In Cancermentioning
confidence: 99%
“…The extra recognition site in the mRNA results in significantly more suppression of the target. In line with TGF-β acting as a tumour suppressor during the early stages of cancer development, a meta-analysis of 39 case–control studies indicated that rs1982073 was significantly associated with breast cancer risk in the Asian population [ 173 ]. In addition to SNPs affecting miRNA:mRNA target recognition, SNPs can also influence the degree of silencing.…”
Section: Mirna Dysregulation In Cancermentioning
confidence: 99%